Edukasi Metode Stimulasi Sumur untuk Peningkatan Produksi Migas di SMK Perminyakan Dumai - Novrianti Novrianti; Doddy Yulianto; Novia Rita; Teguh Sahibullah Fajri; Retno Agustrianingsih (CANANG: Jurnal Pengabdian Masyarakat, 2025)
Well stimulation is one method used to increase oil and gas production rates. Education related to sound stimulation, which involves acidizing and hydraulic fracturing, was conducted during a community service activity by a team of lecturers from the Faculty of Engineering at the University of Riau at the Dumai Petroleum Vocational School. This activity was conducted to enhance students' knowledge and understanding of technological advancements and research developments related to methods for increasing oil and gas production flow rates. The activity consisted of explanations, demonstrations, and discussions related to acidizing and hydraulic fracturing aimed at increasing oil and gas production flow rates. Additionally, the latest research and technology related to sound stimulation were presented to update the students' knowledge on the latest developments in the field of sound stimulation. This activity was well received by the academic community of the Dumai Petroleum Vocational School, as it aimed to enhance the students' knowledge, broaden their horizons, and ultimately prepare them to compete with students from other petroleum vocational schools